An Adolescent with a Rare De Novo Distal Trisomy 6p and Distal Monosomy 6q Chromosomal Combination. (31st August 2020) - Peterman, Leia A.; Vance, Gail H.; Conboy, Erin E.; Anderson, Katelynn; Weaver, David D.
Abstract : We report on a 12-year-old female with both a partial duplication and deletion involving chromosome 6. The duplication involves 6p25.3p24.3 (7.585 Mb) while the deletion includes 6q27q27 (6.244 Mb). This chromosomal abnormality is also described as distal trisomy 6p and distal monosomy 6q. The patient has a Chiari II malformation, hydrocephalus, agenesis of the corpus callosum, microcephaly, bilateral renal duplicated collecting system, scoliosis, and myelomeningocele associated with a neurogenic bladder and bladder reflux. Additional features have included seizures, feeding dysfunction, failure to thrive, sleep apnea, global developmental delay, intellectual disability, and absent speech. To our knowledge, our report is just the sixth case in the literature with concomitant distal 6p duplication and distal 6q deletion. Although a majority of chromosomal duplication-deletion cases have resulted from a parental pericentric inversion, the parents of our case have normal chromosomes. This is the first reported de novo case of distal 6p duplication and distal 6q deletion. Alternate explanations for the origin of the patient's chromosome abnormalities include parental gonadal mosaicism, nonallelic homologous recombination, or potentially intrachromosomal transposition of the telomeres of chromosome 6. Nonpaternity was considered but ruled out by whole exome sequencing analysis.